A Combined Aerobic and Resistance Exercise Program Improves Physical Functional Performance in Patients With Heart Failure: A Pilot Study - Gary, Rebecca A. (2012)
BACKGROUND: Recent guidelines for exercise in patients with heart failure (HF) recommended aerobic and resistance exercise as being safe and effective; however, the clinical and functional significance of these combined training modalities has not been established. In this pilot study, combined aerobic and resistance training was hypothesized to improve physical function, muscle strength, and health-related quality of life (HRQOL) compared with an attention control wait list (ACWL). METHODS: The 10-item Continuous Scale Physical Functional Performance Test (CS-PFP10), which simulates common household chores; muscle strength (handgrip and knee extension); and HRQOL (Kansas City Cardiomyopathy Questionnaire) were evaluated at baseline (T1) and at 12 weeks (T2). The home-based moderate-intensity walking and resistance training program was performed 5 days a week. RESULTS: Twenty-four New York Heart Association class II to III HF patients (mean [SD] age, 60 [10] years; mean [SD] left ventricular ejection fraction, 25% [9%]) were randomized to a combined aerobic and resistance exercise program or to an ACWL group. Of the total group, 58% were New York Heart Association class III HF patients, 50% were white, and 50% were female. The CS-PFP10 total scores were significantly increased in the exercise group, from 45 (18) to 56 (16). The Kansas City Cardiomyopathy Questionnaire overall summary score was significantly improved (P < .001) at T2 in the exercise intervention group compared with the ACWL group. CONCLUSIONS: Participants provided the home-based, combined aerobic and resistance exercise program had significantly improved physical function, muscle strength, symptom severity, and HRQOL compared with the ACWL group. The findings of this study must be interpreted cautiously owing to the limitations of a small sample, data collection from a single center, and differences between control and interventions groups at baseline. A combined aerobic and resistance exercise approach may improve physical function in stable HF patients, but further study in a larger, more diverse population is recommended. However, in this study, the CS-PFP10 instrument demonstrated its ability to identify functional health status in HF patients and thus warrants further testing in a larger sample for possible use in clinical practice.